Food allergen communication: An in-business feasibility trial. (December 2021) - McPhedran, Robert; Patel, Krishane; Rayner, Alice; Patel, Michelle; Disson, Joanna; John, Alice; Porter, Katharine; Thornton, Katie; Toombs, Ben
Abstract: Clear allergen communication in food business operators (FBOs) has been shown to have a positive impact on customers' perceptions of businesses. However, the precise size and nature of this effect is not known: there is a paucity of quantitative evidence in this area, particularly in the form of randomised controlled trials (RCTs). The Food Standards Agency (FSA), in collaboration with Kantar Public UK's Behavioural Practice, conducted a feasibility trial to investigate whether a randomised cluster trial – involving the proactive communication of allergen information at the point of sale in FBOs – is feasible. This was the first such trial conducted in the UK to date. The trial was conducted on-site at ten branches of a multinational FBO, and involved a matched pairs cluster quasi-randomised experiment, with five pairs of branches selected for participation. Results suggest that a fully powered RCT would likely be feasible in the UK. In this case, the primary challenge was the recruitment of FBOs: despite high levels of initial interest from four FBOs, only one took part. However, it is likely that the proliferation of COVID-19 adversely impacted participation. Positively, analysis suggested that delivery of the trial's intervention – proactively asking about customer's food allergies/intolerances – may have a positive effect upon customer's 'trust' in, and 'satisfaction' with, food outlets. This result should be further investigated in future fully powered RCTs. Highlights: A trial to establish the feasibility of in-business randomised cluster trials. Examined the effects of changes in allergen communication in a multinational food business. Results suggest that a fully powered in-business RCT would likely be feasible in the UK. Analysis suggests that asking customers about their allergies/intolerances may have benefits.